If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4y + 2) + -22 = 4(5y + -5) + -14 Reorder the terms: 3(2 + 4y) + -22 = 4(5y + -5) + -14 (2 * 3 + 4y * 3) + -22 = 4(5y + -5) + -14 (6 + 12y) + -22 = 4(5y + -5) + -14 Reorder the terms: 6 + -22 + 12y = 4(5y + -5) + -14 Combine like terms: 6 + -22 = -16 -16 + 12y = 4(5y + -5) + -14 Reorder the terms: -16 + 12y = 4(-5 + 5y) + -14 -16 + 12y = (-5 * 4 + 5y * 4) + -14 -16 + 12y = (-20 + 20y) + -14 Reorder the terms: -16 + 12y = -20 + -14 + 20y Combine like terms: -20 + -14 = -34 -16 + 12y = -34 + 20y Solving -16 + 12y = -34 + 20y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-20y' to each side of the equation. -16 + 12y + -20y = -34 + 20y + -20y Combine like terms: 12y + -20y = -8y -16 + -8y = -34 + 20y + -20y Combine like terms: 20y + -20y = 0 -16 + -8y = -34 + 0 -16 + -8y = -34 Add '16' to each side of the equation. -16 + 16 + -8y = -34 + 16 Combine like terms: -16 + 16 = 0 0 + -8y = -34 + 16 -8y = -34 + 16 Combine like terms: -34 + 16 = -18 -8y = -18 Divide each side by '-8'. y = 2.25 Simplifying y = 2.25
| -1225-12x=-1705 | | x+25+3x=-14-3x-17 | | (x+[x+6])*2=60 | | -7a-1=13 | | 12-4=3n-11n | | -1225-12x=0 | | -15+2x=21-x+4x | | 2x+x=160 | | 6(3x-2)=5(2x-2) | | x+(x+6)*2=60 | | -3(5k+8)=-24 | | -13=-h-(7) | | 17x+x+3x= | | 3(X+2)-(2X-7)=-(5X-1)-2(X+6) | | 6x=2y | | x(x+6)*2=60 | | 2y=-30 | | 10-3b=1-6b | | 5x-[2+3(1-x)]=2x+2(x-1) | | 5u^2+(-9u)+2=0 | | 7x^2+6x+4=0 | | 2(n+6)=-n | | .45+18n=441 | | 9h-3h=15 | | 2(3x+6)+4(4x+5)+3=22x+36 | | 4x^2+120=120 | | x^2+14x=1715 | | 3x=4+3x+x | | 5u^2-9u+2=0 | | 2*A+A^2=0.1 | | 9x=-10 | | 7N-10-9=-13 |